Serum steroid profiling of hepatocellular carcinoma associated with hyperadrenocorticism in dogs: A preliminary study - Oo, Thandar; Sasaki, Noboru; Ikenaka, Yoshinori; Ichise, Takahiro; Nagata, Noriyuki; Yokoyama, Nozomu; Sasaoka, Kazuyoshi; Morishita, Keitaro; Nakamura, Kensuke; Takiguchi, Mitsuyoshi (Frontiers in Veterinary Science, 2022)
Background: Hepatocellular carcinoma (HCC) is one of the most common primary liver tumors in humans and dogs. Excessive adrenocortical hormones exposure may cause steroid hepatopathy, which may develop into HCC. In our previous study, hyperadrenocorticism (HAC) was a highly concurrent disease in dogs with HCC. Therefore, this study hypothesized that adrenal steroid alterations might be involved in hepatocarcinogenesis and aimed to specify the relationship between HAC and HCC in dogs. Materials and methods: This study included 46 dogs brought to the Hokkaido University Veterinary Teaching Hospital between March 2019 to December 2020. Owners gave their signed consent for blood collection on their first visit. A total of 19 steroids (14 steroids and 5 metabolites) in the baseline serum of 15 HCC, 15 HAC and 10 dogs with both diseases were quantitatively measured using the developed liquid chromatography coupled with tandem mass spectrometry (LC/MS/MS) method. Results: In each group, 11 steroids were detected higher than 50%. The detection rate of steroid hormones did not significantly differ between the groups (p>0.05). Principle component analysis showed that the steroid profiles of three groups were comparable. Median steroid hormone concentrations were not significantly different between the study diseases (p>0.05). Conclusions: The developed LC/MS/MS was useful for measuring steroid hormones. Although it was clear that HAC was concurrent in HCC dogs, none of the serum steroids were suggested to be involved in HCC.